Who has the right to travel during peak hours? On congestion pricing and 'desirable' travellers. (April 2018) - Vanoutrive, Thomas; Zijlstra, Toon
Abstract: Congestion pricing concerns the right to travel during peak hours. Most proponents of pricing propose an impersonal and anonymous allocation mechanism based on the willingness-to-pay of the person who travels. This view builds on the concept of private property rights and we confront this view with a different conception of rights, one based on needs. Furthermore, we discuss the results of an illustrative experiment in which respondents allocate access rights to hypothetical travellers. We can conclude that replacing individual self-judgment by judgments of others offers a fresh perspective on congestion pricing. Highlights: Normative reasoning could be taken more seriously in debates on congestion pricing. Congestion pricing studies would benefit from a more social and relational perspective. Sending car users priced off the road to transit is unfair towards captive users.